2019
DOI: 10.3791/60055
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Learning and Memory Ability in an Alzheimer's Disease Mouse Model using the Morris Water Maze

Abstract: A Morris water maze (MWM) experiment forces experimental animals to swim and learn to find a platform hidden in the water. It is widely used in scientific research to assess the learning and memory of animals. Due to the extensive use of the MWM test, visual experimental protocols are essential for researchers. This manuscript uses the latest studies to introduce the protocol of the MWM test. Alzheimer' Disease (AD) is characterized by a progressive loss of memory and cognitive function. An alternative and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 10 publications
(13 reference statements)
3
28
0
Order By: Relevance
“…Cognitive dysfunction has been documented as one of the complications of diabetes, suggesting a close link between diabetes and AD (Jash et al, 2020 ). One of the main symptoms of AD is impaired memory (Sharma et al, 2020 ); therefore, to test whether the memory is altered in mice after the injection of AGEs, we conducted the Morris Water Maze, Y-maze, and open field tests and found that the memory of AGE mice decreased significantly and anxiety behavior increased, which is consistent with previous AD research (Tian et al, 2019 ; Du et al, 2020 ). Subsequently, to further study whether the brain of AGE mice can develop AD symptoms, we assessed the expression of AD-related proteins such as P-tau and APP, which were significantly increased in the hippocampus of AGE mice.…”
Section: Discussionsupporting
confidence: 85%
“…Cognitive dysfunction has been documented as one of the complications of diabetes, suggesting a close link between diabetes and AD (Jash et al, 2020 ). One of the main symptoms of AD is impaired memory (Sharma et al, 2020 ); therefore, to test whether the memory is altered in mice after the injection of AGEs, we conducted the Morris Water Maze, Y-maze, and open field tests and found that the memory of AGE mice decreased significantly and anxiety behavior increased, which is consistent with previous AD research (Tian et al, 2019 ; Du et al, 2020 ). Subsequently, to further study whether the brain of AGE mice can develop AD symptoms, we assessed the expression of AD-related proteins such as P-tau and APP, which were significantly increased in the hippocampus of AGE mice.…”
Section: Discussionsupporting
confidence: 85%
“…In experiments with AD animal models, the MWM assay is commonly used to detect the learning ability and memory of the animals (Baeta-Corral and Giménez-Llort, 2015; Gong et al, 2019;Sun et al, 2019). In this study, APP/PS1 doubletransgenic mice and Aβ 25-35 -injected mice were subjected to the MWM test, and they had obvious cognitive dysfunction, consistent with the behavioral phenotype of the AD animal model (Tian et al, 2019).…”
Section: Discussionmentioning
confidence: 65%
“…Compared to the Non-Tg, the Tg group exhibited notably fewer platform crossings and spent markedly less time in the SW quadrant. The shorter time spent by the APP/PS1 mice in the SW quadrant, which had been the location of the platform, implies that they exhibited worse memory (Tian et al, 2019). The Tg + EA group stayed obviously longer in the SW quadrant than the Tg group (Figures 2B,C).…”
Section: Effect Of Ea On the Cognitive Abilities Of App/ps1 Micementioning
confidence: 97%